Temporal differences between high vowels and glides are more robust than spatial differences. (September 2021) - Burgdorf, Dan Cameron; Tilsen, Sam
Highlights: EMA imitation study of high vowels and glides. High vowels and glides show nonlinear (categorical) temporal differences. Both [i]-[j] and [u]-[w] differ in extrinsic gestural organization. [u]-[w] additionally show an intrinsic difference of gestural stiffness. Less variance in articulatory measures for glides than vowels; reverse for acoustic. Abstract: It is often taken for granted that the glides [j] and [w] differ from their high-vowel counterparts [i] and [u] by having a greater degree of constriction and shorter duration. Yet there is little phonetic research to support these assumptions. Furthermore, although phonological patterns indicate that vowels and glides can be distinct phonemic categories, the extent to which their phonetic properties are categorically distinguished by speakers is unknown. We conducted an experiment to investigate articulatory and acoustic differences between productions of English vowels and glides at palatal and labio-velar places of articulation, in which participants imitated ambiguous intervocalic stimuli which varied in duration and intensity. The results showed that all speakers manipulated temporal aspects of their imitations of both palatal and labio-velar targets, while only some speakers manipulated constriction degree, and only for the labio-velars. This finding suggests that temporal organization may be more important than constriction degree for the glide-vowel distinction. Furthermore, temporal variables were often non-linearly related to stimulus duration, supporting the hypothesis that there exists a categorical difference in the temporal organization of articulatory gestures for vowels vs glides.